Reestructuración organizacional a través de la gestión por procesos para la prestación de servicios en un Hostal de la Provincia de Pichincha - Pazmiño Iza, Verónica de las Mercedes (2007)
"Achieving a strong position in the market through the systematization of processes to drive growth in the hotel within the national and international industry, for which it was necessary to rely on the specific objectives. "Optimize material and human resources to the implementation of technology and staff training, to enable us expedite the process and ensure quality of service." "Develop a promotional plan based on the strengths and opportunities of the company, taking into consideration the criteria presented by the Hospitality Industry that in order to improve the care of customers."